Prognostic impact of the controlling nutritional status score in patients with hematologic malignancies: A systematic review and meta-analysis - Lu, Chuanyang; Chen, Qiuni; Fei, Linrong; Wang, Junhui; Wang, Chunling; Yu, Liang (Frontiers in Immunology, 2022)
BACKGROUND: An increasing number of studies have validated the prognostic significance of the controlling nutritional status (CONUT) score in patients with solid tumors. However, the extent of the correlation between the CONUT score and clinical outcomes of patients with hematologic malignancies is unclear. OBJECTIVE: This study aimed to investigate the prognostic role of the CONUT score in patients with hematologic malignancies. METHODS: All relevant articles published up to November 15, 2021, were identified by systematically searching PubMed, Embase, Web of Science, and Cochrane Library. Pooled hazard ratios (HRs) and 95% confidence intervals were used to quantitatively analyze the association between the CONUT scores and clinical outcomes of patients with hematologic malignancies. Subgroup and sensitivity analyses were performed. Funnel plots as well as Begg's and Egger's tests were used to assess publication bias. RESULTS: Six studies with 1811 patients were included in the meta-analysis. The results showed that a high CONUT score was associated with worse overall survival (OS) (HR=1.34, 95%CI 1.14-1.59, P < 0.001) and progression-free survival (PFS) (HR=1.20, 95%CI 1.10-1.32, P < 0.001). CONCLUSIONS: The CONUT score is an independent unfavorable prognostic factor in patients with hematologic malignancies.